The Role of Dopamine in Schizophrenia from a Neurobiological and Evolutionary Perspective: Old Fashioned, but Still in Vogue - Brisch, Ralf; Saniotis, Arthur; Wolf, Rainer; Bielau, Hendrik; Bernstein, Hans-Gert; Steiner, Johann; Bogerts, Bernhard; Braun, Katharina; Jankowski, Zbigniew; Kumaratilake, Jaliya; Henneberg, Maciej; Gos, Tomasz (Frontiers in Psychiatry, 2014)
Abstract: Dopamine is an inhibitory neurotransmitter involved in the pathology of schizophrenia. The revised dopamine hypothesis states that dopamine abnormalities in the mesolimbic and prefrontal brain regions exist in schizophrenia. However, recent research has indicated that glutamate, GABA, acetylcholine, and serotonin alterations are also involved in the pathology of schizophrenia. This review provides an in-depth analysis of dopamine in animal models of schizophrenia and also focuses on dopamine and cognition. Furthermore, this review provides not only an overview of dopamine receptors and the antipsychotic effects of treatments targeting them, but also an outline of dopamine and it`s interaction with other neurochemical models of schizophrenia. The roles of dopamine in the evolution of the human brain and human mental abilities, which are affected in schizophrenia patients, are also discussed.